The Secrets of Attraction : Decoding Body Language to Maximize your Sex Appeal - Lloyd-Elliott, Martin (London Hamlyn, 1994)
Shows how to enhance one's own body language, as well as how to interpret that of others. It uses examples from real-life situations, such as in the office or at a party, to help the reader analyze different types of behaviour and to know when signals are unintentional, false or genuine
Include Color Illustration and Bibliography
Keywords: Nonverbal communication